Writing in mathematics enhanced by technology - Habre, Samer (2011)
Research on writing in mathematics has shown that this skill is most beneficial when it is directed at the learning aspect. Educators agree that writing benefits in the promotion of understanding in an inquiry based environment. This skill however necessitates proficiency on the part of the students that may not have been developed at their earlier learning stages. But the burden placed on teachers and learners to master this skill is rewarded by the mathematical learning in such an environment. This paper explores the effect of writing on improving student understanding of some topics in differential equations and investigates how the students’ writing skills developed throughout the semester.